Tolerance and Recognition, Proposal of a Conceptual Arc - Giusti, Miguel (2005)
In the current political circumstances. the concept of "tolerance" has recovered a relevant academic dignity and has been the topic of numerous investigations. Notwithstanding, "tolerance" is still being considered a "blurred" or "evasive" virtue. In this paper. the A. propases a systematic interpretation of that notion, in order to establish a body of henneneutic matrixes that may shed light on its reach and limitations. In this analysis, tolerance tums out to be a "parasitic" notion. for its validity always depends on a previous moral conception, of an affirmative and declarative nature. In that sense, the A. suggests that the new paradigm of "recognition" may serve as the ultimate and teleological normative framework of the nolion of tolerance.